Review of Pathophysiological Aspects and Risk Factors for Liver Dysfunction - Hossam El-Din M Omar; Omnia HM Omar; Gamal Badr (Archives of Clinical Gastroenterology - Peertechz Publications, 2016)
The liver is accountable for many critical functions within the body and loss of those functions can cause signifi cant damage to the body. Liver disease is a extensive term that covers all aspects that cause the liver to fail to perform its proper functions. Acute liver failure indicates the development of severe acute liver injury with impaired synthetic function without preexisting of clinical liver disease. However, chronic liver disease is characterized by destruction of the hepatic tissue. Early changes, such as fatty liver can progress via infl ammation and fi brosis to cirrhosis. The main causes for liver dysfunction  includedyslipidemia, obesity, viral and parasitic infection, drugs and environmental pollution, alcohol abuse, autoimmunity, and genetic defective such as hemochromatosis. The present review almost covers all the previous aspects that lead to liver dysfunction.